Women’s Empowerment: Discovering Women’s Subjectivity in Arabic Novels Based on Juliet Mitchell’s Feminist Psychoanalysis - Nur'aini, Aisyah; Basid, Abdul (Center of Language and Cultural Studies, 2024)
As women play an important role in shaping the character of a quality generation, women’s empowerment is an investment for a better future. This study aims to; 1) reveal women’s subjectivity in Juliet Mitchell’s feminist psychoanalysis perspective; 2) analyze the role of women’s empowerment reflected to female characters; and 3) explore the dynamics between social structure, culture, and psychology of female characters in the novel Zeina by Nawal El Saadawi This research uses a descriptive-qualitative method. The data source of this research is the novel “Zeina” by Nawal El Saadawi and complemented by theoretical and other references that have relevance. Data collection techniques use translation, reading and note-taking techniques. Data analysis techniques use the Miles and Huberman models. The results of this study show that; 1) the subjectivity of female characters in the novel “Zeina” includes; identity differences, resilience and self-formation, internal and external conflicts, and struggles for emancipation and freedom 2) The role of empowerment reflected in female characters, includes; women becoming entertainers, women becoming magazine leaders, and women becoming literary critics as well as department heads. 3) The dynamics that occur between social, cultural, and psychological structures of female characters are; the influence of trauma in identity formation, identity reconstruction, and identity transformation through trauma healing. This research confirms that women can empower themselves, even in a patriarchal environment. Empowerment through education, employment, and psychological support is important as a foundation for women’s role as agents of change.